PRINSIP INDIVIDUALISASI PIDANA DALAM HUKUM PIDANA DAN HUKUM PIDANA ISLAM DI INDONESIA - Tri Wahyu Widiastuti (Universitas Slamet Riyadi, 2010)
Abstract : Criminal is suffering intentionally charged to people who perform acts that meet certain requirements. Crime is also a reaction to these offenses and the intangible of a deliberately inflicted suffering to the makers of offense. Giving criminal should be based on the principle of individualization of criminal, where the provision or the imposition of criminal sanctions should consider the error and state criminals. it is important that criminal sanctions are considered fair to the perpetrator, victim and community. Key words : individualization of criminal